VSTO for mere mortals : a VBA developer's guide to Microsoft Office development using Visual studio 2005 tools for Office - McGrath, Kathleen (Addison-Wesley, 2006)
Praise for VSTO for Mere Mortals "This is the book I wish I'd had when I was first introduced to VSTO and the .NET Framework. It will be invaluable not only to those considering VSTO, but for anyone transitioning from Office VBA to Visual Basic.NET. The wide range of subjects covered provides an entry point for the more in-depth, developer-oriented documentation available on MSDN and elsewhere." - Cindy Meister, MS Word MVP " VSTO for Mere Mortals does a great job of building a bridge between the worlds of VBA and VSTO. Kathleen and Paul show how a VBA developer can have the richness of Office and also the power, maintainability, and security of Visual Studio. They succeeded in writing a book that is approachable, understandable, and compelling." - KD Hallman, General Manager, Microsoft, Developer Division "This book is an excellent choice for VBA developers looking to make the switch to .NET development for Office using Visual Studio Tools for Office. In many instances VB.NET code is presented alongside equivalent VBA code to help illustrate key conceptual and usage differences." - Steve Hansen, OfficeZealot.com, author of Mastering Excel 2003 Programming with VBA and coauthor of Mastering Excel 2000 Premium Edition "Visual Studio 2005 Tools for Office is the way to go for building managed Office applications. If you're moving from VBA to managed code, this book shows you the way." - Ken Getz, Senior Consultant, MCW Technologies, LLC "This book is highly recommended for VBA developers who are interested in doing Office programming using the rich power of Visual Studio and .NET." - Mei Liang, Software Design Engineer in Test, Microsoft "Kathleen McGrath has stuffed VSTO for Mere Mortals with in-depth code samples that demonstrate VSTO in an easy-to-understand way. From simple how-to's to advanced functionality, it's all here. I learned a great deal from reading this book." - Justin Whitney, Technical Journalist "This book provides an instantly accessible resource for VBA and Office developers to become familiar with the powerful new Office development platform, but even goes beyond that, providing a number of 'worth the purchase of the book' tips, fully functional examples, and elegant methods from someone who has obviously spent a lot of time with these tools to help the mortal on the path to becoming a guru." - Rory Plaire, Solutions Architect, DigitalCommons LLC.